Deliberate or Instinctive? Proactive and Reactive Coping for Technostress. Issue 4 (2nd October 2019) - Pirkkalainen, Henri; Salo, Markus; Tarafdar, Monideepa; Makkonen, Markus
Abstract: Employees in organizations face technostress that is, stress from information technology (IT) use. Although technostress is a highly prevalent organizational phenomenon, there is a lack of theory-based understanding on how IT users can cope with it. We theorize and validate a model for deliberate proactive and instinctive reactive coping for technostress. Drawing from theories on coping, our model posits that the reactive coping behaviors of distress venting and distancing from IT can alleviate technostress by diminishing the negative effect of technostress creators on IT-enabled productivity. The proactive coping behaviors of positive reinterpretation and IT control can help IT users by influencing the extent to which reactive coping behaviors are effective and by positively influencing IT-enabled productivity. The findings of a cross-sectional survey study of 846 organizational IT users support the model. The paper provides a new theoretical contribution by identifying ways in which organizational IT users can cope with technostress.